Jama’ah Response to The Art of The Imam’s Tilawah in The Reading of Prayers in The Pekanbaru City Mosque - Arman, Idawati; Anwar, Armansyah; Soemary, Sudirman; Rusdi, Khoirun Nisa (Perspektif Pendidikan dan Keguruan, 2024)
This research aims to look at the musical aspects contained in the imam's recital of recitations during congregational prayers. Apart from that, this research also aims to see the response of the congregation when attending congregational prayers. In order to obtain data related to the intended objectives, researchers used qualitative methods. The data collection techniques used were interviews, observation and documentation. Interviews were conducted with two mosque imams who have good recitation skills, as well as several mosque congregation members who are members of the Subuh Warriors community. From the results of the analysis, it was concluded that the rhythm of the recitation songs commonly used by the two imams in question were the bayati and jiharka rhythms. The results of the analysis of the congregation's response were past responses, future responses and current responses. These various responses are shown through the reactions that emerge from each congregation. The differences in responses that lead to this reaction are caused by differences in spiritual experiences, including personal life experiences and religious experiences that have been experienced.